Cell-cell communication via ciliary extracellular vesicles: clues from model systems - Wang, Juan (Essays Biochem, 2018)
In this short review, we will focus on the uniqueness of ciliary extracellular vesicles (EVs). In particular, we will review what has been learned regarding EVs produced by cilia of model organisms. Model systems including Chlamydomonas, C. elegans, and mouse revealed the fundamental biology of cilia and flagella and provide a paradigm to understand the roles of cilia and flagella in human development, health, and disease. Likewise, we propose that general principles learned from model systems regarding ciliary EV biogenesis and functions may provide a framework to explore the roles of ciliary EVs in human development, health, and disease.